Choice of a General Anesthesia Technique in the Surgical Treatment of Postinfarct Left Ventricular Aneurysms - N. A. Karpun; V. V. Moroz; D. L. Kranin; A. I., Gridasov; A. A. Mikheyev; Yu. V. Khrenov; R. S. Ovcharov (Общая реаниматология)
Objective. To choose the optimum technique of general anesthesia in the surgical treatment of patients with postinfarct left ventricular aneurysms (PLVA).Materials and methods. Fifty-four patients operated on for PLVA were examined. They were divided into 4 groups according to the basic technique of general anesthesia: 1) intravenous anesthesia based on propofol and fentanyl; 2) inhalation sevoflurane anesthesia with fentanyl enhancement of the analgesic component; 3) inhalation isoflurane anesthesia with fentanyl enhancement of the analgesic component; 4) general anesthesia in combination with epidural blockade. Central hemodynamics was investigated by the thermodilution technique and the perioperative period was also studied.Results and discussion. None of the general anesthesia techniques affected the development of perioperative complications. However, with decreased myocardial reserves, high thoracic epidural anesthesia should be applied with caution as it causes a significant desympathization, which may lead to impairments of the autoregulatory mechanisms of coronary blood flow and aggravate existing contractile disorders. Intravenous and inhalation anesthesia techniques provide a fair hemodynamic stability at all stages of surgical treatment. Inhalation anesthesia has a number of advantages: less cost and the possibility of rapid activation of patients in the early postoperative period.